PENGARUH KONFLIK KERJA KELUARGA, AMBIGUITAS PERAN, DAN STRES KERJA TERHADAP KINERJA PEGAWAI - Nurhaini Nurhaini; Abdul Kodir Djaelani; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to find out and analyze the effect of work family conflict, role ambiguity, and work stress on employee performance in female employees of Malang City Regional Water Companies/PDAMs both partially and simultaneously. This research was conducted using a questionnaire distributed through random sampling techniques with a sample of 75 people who were female employees of Regional Drinking Water Companies/PDAMs in Malang City. Data analysis in this study used SPSS (Statistical product and service solution) assistance with the data testing techniques used were validity test, reliability test, classic assumption test, partial test (t) and simultaneous test (F). The results showed that work family conflict, partially influential and significant effect on employee performance and the value obtained from the coefficient of determination that was not used in this study showed that work family conflict on employee performance has positive effects, role ambiguity, and stress work partially influences and is significant on employee performance, while simultaneously family work conflict, role ambiguity, and work stress influence and significantly affect employee performance.Keywords: Work Family Conflict; Role Ambiguity; Work Stress; Employee Performance